Vertebral sarcoidosis mimicking metastasis on Magnetic resonance Imaging - Amandeep Singh,; Aaina Devgan,; Tanveen Kaur,; Gauravdeep Singh, (Indian Journal of Case Reports, 2021)
Vertebral sarcoidosis is a rare condition that can present with persistent back pain, often with concurrent lung, lymph node, or skin involvement. It can produce lytic or blastic osseous lesions that are indistinguishable from metastatic cancer on bone scan and magnetic resonance imaging (MRI). Here, we present the case of a 65-year-old woman who presented with persistent severe low back pain which progressed gradually and was refractory to usual medical treatment after spontaneous resolution of Stage I pulmonary sarcoidosis. MRI of the spine showed lytic thoracic and lumbar vertebral lesions.